2017
DOI: 10.1186/s12884-017-1276-x
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers to uptake and adherence to lifelong antiretroviral therapy among HIV infected pregnant women in Uganda: a qualitative study

Abstract: BackgroundIn 2012, Uganda started implementing lifelong antiretroviral therapy (ART) for prevention of mother to child transmission (PMTCT) in line with the WHO 2012 guidelines. This study explored experiences of HIV infected pregnant and breastfeeding women regarding barriers and facilitators to uptake and adherence to lifelong ART.MethodsThis was a cross-sectional qualitative study conducted in three districts (Masaka, Mityana and Luwero) in Uganda, between February and May 2014. We conducted in-depth interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
123
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(149 citation statements)
references
References 7 publications
18
123
0
2
Order By: Relevance
“…Frequently mentioned individual and family related factors identified in this study were fear of divorce, lack of family support, lack of partner support and lack of time. Like our research, other studies found that non-disclosure of HIV status, fear of divorce, fear of HIV stigma, and lack of partners support were some of the most common barriers to PMTCT service utilization [16,[19][20][21][22][23][24][25][26]. Another study in Sudan [27], and in Malawi [28] also revealed that women are not likely to disclose their HIV status due to stigma.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Frequently mentioned individual and family related factors identified in this study were fear of divorce, lack of family support, lack of partner support and lack of time. Like our research, other studies found that non-disclosure of HIV status, fear of divorce, fear of HIV stigma, and lack of partners support were some of the most common barriers to PMTCT service utilization [16,[19][20][21][22][23][24][25][26]. Another study in Sudan [27], and in Malawi [28] also revealed that women are not likely to disclose their HIV status due to stigma.…”
Section: Discussionsupporting
confidence: 72%
“…In our study, the main reasons for women not taking PMTCT service mentioned by health workers were disclosure of the result, fear of partner, drug side effect, drug supply interruption, trained health care professional not giving attention to the work and work load. Other studies have also had similar findings [18,19,28].…”
Section: Discussionsupporting
confidence: 70%
“…Having a treatment supporter may be an indication of HIV disclosure, which has been shown to be strongly associated with an individual's ability for sustained engagement in HIV care. 12,[22][23][24][25] Disclosing one's HIV status enables one to garner social support and removes the element of secrecy; women who have disclosed their HIV status are more likely to show up to their appointments without fear. [25][26][27][28] The present study relied on routinely collected clinical data, which did not include details about the characteristic of the treatment supporter, including the individual's relationship with the patient and the type of support they provide.…”
Section: Discussionmentioning
confidence: 99%
“…The classification of a country as an LMIC was determined based on the 2018 World Bank classification criteria [7]. The Covidence tool was used to remove duplicate studies and to conduct study screening [8]. Two reviewers (ARM and CK) reviewed all titles and abstracts independently, followed by independent full text review of remaining articles.…”
Section: Methodsmentioning
confidence: 99%